2016
DOI: 10.30958/aje.3-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of Parents and Care Professionals in Cases of Children Placed in Residential Care Homes – Parental Perspective

Abstract: The paradigm of residential child care, providing education and care for children outside the family is changing worldwide. The emphasis is shifting from a narrow child-focused approach to a more child-and-family centred one, foregrounding the quality of collaboration between parents and everyone involved in the child's care. Several Slovenian studies draw attention to the difficulties of maintaining a collaborative partnership with parents that is based on trust and contact. We introduce the findings of a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As reported in the introduction section, a number of researchers have reported lower academic achievement among adolescents with a disability or a chronic condition. While research has proposed that parents' high achievement expectations are a source of distress (Rapus-Pavel et al, 2018), low expectations shape academic skills negatively in young adolescents with a disability (McCoy et al, 2016). Hence, lower academic achievement among young people with a disability or a chronic condition may be a result of parents' lower academic achievement expectations, while high achievement expectations may cause distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in the introduction section, a number of researchers have reported lower academic achievement among adolescents with a disability or a chronic condition. While research has proposed that parents' high achievement expectations are a source of distress (Rapus-Pavel et al, 2018), low expectations shape academic skills negatively in young adolescents with a disability (McCoy et al, 2016). Hence, lower academic achievement among young people with a disability or a chronic condition may be a result of parents' lower academic achievement expectations, while high achievement expectations may cause distress.…”
Section: Discussionmentioning
confidence: 99%
“…Parental expectations predicted high school graduation with a high school diploma among adolescents with learning disabilities but not among adolescents with intellectual disabilities. Furthermore, research showed that mothers' high achievement expectations were a source of distress among dyslexic adolescents (Rapus-Pavel et al, 2018). All but one of these studies used parent-reports of parental academic expectations.…”
Section: Parental Expectations Of Student Achievementmentioning
confidence: 99%